An Analysis of Speech Act in the Animation Movie: Coco - Marlina, Marlina; Wulansari, Dina; Santia, Ine; Rakhmyta, Yunie Amalia (Indonesian Journal Publisher, 2024)
Linguistic aspects are very important in English. When linguistics became a linguistic science, people studied it in several branches of linguistics, including phonetics, phonology, morphology, semantics, sociolinguistics, and Practical. Speech act is one of the important components of pragmatics because speech act is a branch of pragmatics, related to all types of utterances made by speakers and its meaning depends on the point of view of the speaker. speaker and interlocutor. Speech acts are divided into three types: speech, speech, and speech. As technology advances, more media can support the learning process making it more enjoyable. Like learning by reading novels, watching movies and even listening to songs. This search is an analytical speech act introduced by Searle in Cartoons: Coco. The problem of this research is: what types of speech acts are proposed by the main characters in cartoons: Coco and what is the most dominant speech act among the main characters in cartoons: Coco. This study employed a descriptive qualitative methodology. With the qualitative descriptive method, information is gathered via the use of words and images rather than figures. Interviews, field notes, photos, videotapes, private documents, notes or memos, and other documents can all provide data. The author of this research does a case study, provides a basic description, and goes over the language. Because the study's focus is on natural events or symptoms, the author employs this kind of qualitative research in it. The author of this paper will examine Coco, the cartoon's primary character, through an analysis of her verbal acts. Results of the study is: to explore the type of speech act that the main character proposes in the cartoon: Coco and to find out which speech act is most dominant among the main characters in an animated film: Coco. In this study, the author only focuses on studying one type of linguistic behavior, which is linguistic behavior.